10.1016/s1541-9800(08)70497-6 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: There is ongoing debate about how best to deliver anatomy teaching in a modern medical curriculum. Some studies suggest that the separation of basic sciences and clinical teaching can impact students' confidence in anatomy, which has potential long-term implications on their medical career. This suggests new pedagogic approaches to improve anatomy teaching may be beneficial. This study aimed to establish if integrating a clinical case into anatomy practical classes would improve students' anatomy recall compared to anatomy teaching alone. APPROACH: A ten minute clinical scenario was developed, which focused on the typical history, examination, investigations and management of a hip fracture patient. Medical students (n = 220) currently studying lower limb anatomy were randomised by pre-assigned anatomy groups to become intervention or control. In the intervention group, students received the clinical case teaching, followed by their anatomy session. In the control group, students attended the anatomy session. Students in both groups were then assessed on hip anatomy. The intervention group also gave their perception of the clinical case. EVALUATION: This study showed that participants who received integrated teaching performed significantly better in the anatomy recall test (3.64 SD ± 0.574) than whose who had anatomy teaching only (1.95 SD ± 0.994) (chi2 = 185.51, p < 0.00001). Most participants (93.5%; 101/108) strongly agreed/agreed that integrating clinical cases into anatomy teaching benefited their learning. IMPLICATIONS: These results suggest that students' anatomy recall may be improved by integrating clinical cases and anatomy teaching. It also suggests that students found this approach beneficial for their learning.